Acmeological approach to physical education of students of secondary schools in the aspect of personality-oriented training - Y.V. Vas'kov (H.S. Skovoroda Kharkov National Pedagogical University, 2015)
Purpose : to identify the main ways to use acmeological approach to physical education students of secondary schools. Material : government documents, questionnaire, research scientists, monitoring the activities of teachers-practitioners. Results : identified actual problems of physical education of students. Theoretical aspects and conditions of implementation in a real learning process acmeological approach. The problems of setting goals and objectives to students considering acmeological approach. The approach includes the selection of a modern sports education content. Also, forms, methods and teaching aids that optimize the learning activities of each student. Proposes a system of evaluation of students' achievements based on acmeological approach. Examines the role of physical education of teachers to introduce acmeological approach in the learning process. Conclusions : the main aspects of acmeological approach to the organization of educational process on physical training. It is proposed to develop the content of sports education based on general didactic approaches. Approach that includes four components of social experience. The components of the educational process technology for physical culture. It is proposed to modernize the methods, forms and means of improving the system of assessing students' achievements in an integrated manner.